Pengukuran Kinerja Tenaga Profesional Pada Organisasi Jasa (Studi Kasus Kotabahasa Salatiga) - Devitia Putri Nilamsari (Universitas Katolik Soegijapranata, Semarang, 2018)
This research aimed to describe the performance measurement and the basic indicators of performance measurement the professionals in family organization, especially in the service sector. As the strategy of depth-case study, this research uses a qualitative approach to describe the process or application of performance measurement and the basic indicators of performance measurement in Kotabahasa Salatiga. The results show that the process of performance measurementin Kotabahasa Salatiga starts from initial stage of microteaching selection which is the basic of initial performance measurement and placement for the teachers, then continued to the assessment of the teachers’ daily behavior through observation, review to the class or criticsm from students. In addition, the basic indicators of the teachers’ performance measurement are discipline, responsibility for task or job, capability both technical and conceptual and the interpersonal relationship. Based on the performance measurement, the management of Kotabahasa Salatiga gets feedback that can improve the quality and performance of organization and also be able to assess the final result whether the activities that have been planned and implemented so far as fit or not. And then, it is directing teachers to work productively and professionally so that the performance will be more satisfactory and fit with the work’s standards.